Characterization of fly ash solid-waste for low-cost insulation refractory bricks - Debnath N.K.; Acharya V.; Jangu S.; Singh P.; Majhi M.R.; Singh V.K. (My University, 2025)
Fly ash from Barsingsar, Bikaner thermal power plant in northern India, is significantly generating solid-waste. In India, coal is of poor quality having high ash content around 30-45 wt%, fly ash created at coal thermal power plants. The present work investigates the possible use of fly ash solid-waste for the research of insulation refractory bricks. Fly ash is considered as a powdered material being collected by dust collectors built-in boilers of thermal power plants with the use of coal as a fuel. The chemical, thermal, crystallographic and morphological analysis of fly ash solid-waste has been determined by XRF, DTA-TG, XRD and SEM, respectively. The XRF results show the fly ash solid-waste is alumina and silica-rich. XRD results also reveal that the material is composed of mullite and quartz crystals. SEM investigation exhibits the morphology of fly ash solid-waste is needle-like mullite and fibrous-like quartz type of structure, which supports the XRD results. It can be concluded from the inquiry that fly ash solid-waste is the potential low-cost raw material for insulation refractory bricks. © 2021 Elsevier Ltd. All rights reserved.